FORMULASI SEDIAAN HAIR TONIC EKSTRAK ETANOL DAUN KELOR (Moringa oleifera Lamk.) DAN DAUN RAMBUTAN (Nephelium lappaceaum L.) TERHADAP PERTUMBUHAN RAMBUT - Siti Hindun; Nopi Rantika; Aji Najihudin; Acep Indra (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
Moringa olifera lamk and Nephelium lappaceaum L leaves are empirically widely used to stimulate hair growth. The purpose of this research is to combine the kelor leaf extract and rambutan leaf extract formulated in hair tonic. The hair tonic preparations made were evaluated by performing a physical test of the preparation and knowing the best concentration of kelor leaf extract and rambutan leaf extract on rabbit hair growth. The hair tonic were orepared in 3 formulations with the ratio of kelor leaf exract and rambutan leaf extract (1:3 , 1:1 and 3:1)% w/v. the positive control used is hair tonic Minoxidil 2%. Physical tests of the preparation include organoleptic test, pH test, homogeneity test and Viscosity test. Hair growth activity on the 3 rabbits shaved hair and hair growth measurements until the 28 st day. The data of growth measurements were tested statistically by ANOVA test metode. Based on the reseach result, in can be concluded that hair tonic combination of kelor leaf extract and rambutan leaf extract with ratio (1:1)%, has average hair length 3 cm and hair weight 0,236 g is the optimum concentration in stimulating hair growth aktivity with positive control has average hair length 2,025 cm and hair weigth 0,207 g. Test statistically there was no significant difference between extract and positif control (P < 0,05).